Gelidium adriaticum sp. nov. and Gelidium carolinianum sp. nov. (Gelidiales, Rhodophyta) from the Mediterranean Sea. Issue 4 (4th July 2019) - Perrone, C.; Bottalico, A.; Boo, G.H.; Boo, S.M.; Miller, K.A.; Freshwater, D.W.
ABSTRACT: Identification of small Gelidium species based on morphology is difficult; as a consequence, the name Gelidium pusillum has been used for many small gelidiacean taxa throughout the world. Molecular-assisted identifications, however, are demonstrating that G. pusillum has a more restricted distribution than previously recognised. We used detailed morphological analyses combined with rbc L and cox 1 sequence analyses to identify and assess the phylogenetic relationships of small Mediterranean Gelidium species. These analyses revealed the presence of two new species, G. adriaticum sp. nov . and G. carolinianum sp. nov. Gelidium adriaticum is a closely related sister species to G. pusillum, which was not found amongst our Mediterranean specimens. Gelidium carolinianum has been previously collected outside the Mediterranean, but it was misidentified as G. americanum . Morphological observations and sequence data generated from G. americanum types and other historical specimens clarified the status and distribution of this species. Phylogenetic analyses resolved G. carolinianum as a species in the Mediterranean and warm-temperate northwest Atlantic; whereas, G. americanum occurs in the Caribbean and tropical western Atlantic, and is sister to G. calidum from Brazil and closely related to G. crinale .